Islamic Religious Education as Student Character Development in the Millennial Era - Firman, Firman (Riwayat: Educational Journal of History and Humanities, 2024)
The millennial phenomenon becomes very interesting when faced with the condition of Islamic education in Indonesia. On the one hand, Islamic education has a target and orientation to create perfect human beings. However, on the other hand, at the same time, Islamic education must be able to develop the skills, abilities, potential and behavior of its followers in responding to internal challenges and the challenges of the global world that has opened wide before us. "Hard impacts" will be increasingly felt and it will not be easy to reduce them, when Islamic education has to struggle and struggle with the world of the millennial era. When it comes to millennials, there are several problems that are already facing the world of Islamic education. This research aims to analyze the perspective of Islamic religious education in building student character in the current of globalization in the millennial era. The research method used is a qualitative method with a qualitative-phenomenological approach. The research subjects were Balikpapan University FKIP students who were selected using purposive sampling. The object of this research is students in the role of Islamic Religious Education in the formation of morals and character in the millennial generation era. The data collection techniques used were observation, interviews and documentation. The main instrument in this research is the researcher himself. Testing the validity of the data is carried out by: extending observations, increasing persistence, triangulation,. Data analysis uses the Miles and Huberman interactive model. The research findings show that the role of Islamic religious education for students in the millennial era is seen as the guardian of national and religious values to produce quality Muslim scholars